An Analysis of Code-Mixing Found on Deddy Corbuzier’s Youtube Channel Selected Podcast - Raflis Raflis; Mia Gusnita (Fakultas Sastra Universitas Ekasakti, 2021)
Code-Mixing can occur in all circles of society or social status. Code-mixing found in a language, someone cannot prevent code-mixing. The speaker usually speaks two languages and speaker put words or phrase from other languages in the speech or it can be said that code-mixing can occur in direct or indirect situation. Code-Mixing is the change of one language or two languages into another language. Code-mixing can occur in spoken or written text. Therefore, the researcher wants to know the code mixing contained in selected podcast. This study uses Pieter Mueysken's theory of insertion, alternation, and congruent lexicalization. Researcher used qualitative methods. The purpose of this research is to divide the types and explain code mixing based on reasons and factors. After collecting all the data, the researcher found 257 utterances that contain of code-mixing. Code-mixing contained in the insertion there were 158 data 61, 5%), 81 data of alternation (31, 5%), 18 data of congruent lexicalization (7, 0%). Talking about particular topic there were 3 data (1, 17%), empathy about something there were 4 data (1, 55%), repetition used clarificarion there were 12 data (4, 67%). Message intrinsic factor 2 data (0, 77%).